2022
DOI: 10.1007/s40120-022-00368-2
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Interconnectivity in Multiple Sclerosis: A Narrative Review of Potential Underlying Biological Disease Processes

Abstract: Introduction Fatigue, cognitive impairment, depression, and pain are highly prevalent symptoms in multiple sclerosis (MS). These often co-occur and may be explained by a common etiology. By reviewing existing literature, we aimed to identify potential underlying biological processes implicated in the interconnectivity between these symptoms. Methods A literature search was conducted to identify articles reporting research into the biological mechanisms responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 317 publications
0
11
0
Order By: Relevance
“…MS is associated with a variety of neurological symptoms ( 82 ), including sensory disturbances, visual problems, fatigue, altered balance, cognitive dysfunction, anxiety and depression ( 83 88 ). Many studies have shown that the HPA axis plays an important role in controlling the disease process in MS ( 89 , 90 ), and researchers have also revealed that anxiety and depression are significantly linked to higher levels of cortisol, especially in patients with relapsing-remitting MS ( 91 , 92 ). The previous findings differ from the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…MS is associated with a variety of neurological symptoms ( 82 ), including sensory disturbances, visual problems, fatigue, altered balance, cognitive dysfunction, anxiety and depression ( 83 88 ). Many studies have shown that the HPA axis plays an important role in controlling the disease process in MS ( 89 , 90 ), and researchers have also revealed that anxiety and depression are significantly linked to higher levels of cortisol, especially in patients with relapsing-remitting MS ( 91 , 92 ). The previous findings differ from the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…And techniques targeting M1 could benefit not only fatigue, spasticity and pain as previously described, but might also improve reaction time and manual dexterity. The underlying etiology of fatigue, cognitive impairment, and pain in MS may be similar, and the overlap may be a result of lesions in MS occurring in highly interconnected deep gray matter, whereby their ripple effects may affect a variety of other brain circuits ( 59 ). It has been proposed that PwMS with impairment of hand performance may be correlated with cortico-cortical disconnections due to demyelination or a strict disruption of the motor network caused by neurodegenerative processes ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, MBI mechanisms in PwMS are poorly characterized and may be confounded by abnormal inflammatory mediator profile, monoamine dysfunction, neuronal injury, and network dysfunction [44,45]. Nevertheless, MBIs effectively improve stress, anxiety, depression [46], and fatigue [47] in PwMS, suggesting their potential to improve QoL.…”
Section: Introductionmentioning
confidence: 99%